Use of Manganese Oxide-Coated Sand for the Adsorption of Uranium(VI) Ions from Aqueous Solution Using a Column Mode - Weihua Zou; Jiyun Song; Ke Li; Runping Han (Adsorption Science & Technology)
Continuous fixed-bed studies were undertaken to evaluate the performance of manganese oxide-coated sand (MOCS) as an adsorbent for the removal of uranium(VI) ions from aqueous solution under the effect of various process parameters such as the bed depth, the flow rate, the presence of salt and the initial U(VI) ion concentration. The U(VI) ion uptake by MOCS increased with initial U(VI) ion concentration and bed height, but decreased as the flow rate increased. A shorter breakthrough time was observed in the presence of salt. The experimental data obtained from the breakthrough curves were analyzed using the Thomas model. The BDST model was also applied to predict the service times for other flow rates and initial concentrations. The results showed that the Thomas model was suitable for the description of the whole breakthrough curve, while the data were in good agreement with the BDST model. The columns were regenerated by eluting the bound U(VI) ions with 0.5 mol/ℓ HNO 3 solution after the adsorption studies. MOCS could be re-used to adsorb U(VI) ions at a comparable capacity. Compared to virgin sand, the removal of U(VI) ions from MOCS proceeded more readily.